(untitled) (Proceedings of the European Wave and Tidal Energy Conference, 2025)
Polyurethanes (PU) are widely utilized in marine environments, including tribological applications such as gears and coatings, due to their beneficial properties, including excellent chemical, water/saltwater resistance, UV stability, high strength-to-weight ratio, wear resistance, and vibration absorption. These characteristics make PU well-suited for reducing wear and friction in dynamic components, resisting chemical degradation in seawater, and ensuring long-term performance under variable thermal and mechanical conditions in harsh seawater environments. However, due to the wide variety of PU types with varying properties, their performance can differ significantly, making careful material selection essential for the intended application. This research aims to evaluate the tribological behavior of different PU materials in rack-and-pinion system designed for a wave energy converter (WEC developed by Dutch Wave Power). The study investigates the wear resistance, surface damage and mechanisms, wear debris generation and micro-geometry changes along with the friction characteristic in the contact interface. A representative laboratory wear test for the real-life application was identified after examining the operating tribosystem. Three PU compounds were selected following an initial material screening and subjected to wear testing under conditions replicating the rolling-sliding contact experienced in WEC gear systems. These tests were conducted using a wheel-on-wheel configuration tribometer, simulating real-world contact pressures and rolling velocities representative of mid-wave height scenarios. The contact stress conditions were determined from finite element simulations of the WEC rack-and-pinion system. Synthetic seawater lubrication was continuously supplied during tests and introduced in the contact to replicate the seawater environment. Key operational parameters, including rotational slip, friction force, and surface temperatures, were monitored throughout the experiments. Post-mortem investigations included weight measurements, 3D surface topography analysis, and microscopic imaging to assess surface damage, material degradation and wear debris generation. To further analyze the sliding friction phase of rolling-sliding contact, complementary pin-on-disk tests were performed in a seawater-lubricated environment. These tests revealed a decreased coefficient of friction in seawater compared to dry conditions. The adhesion effects originating from same-material pair contacts were mitigated by the lubrication efficiency and regime. The original surface roughness and the pressure–velocity values influenced this phenomenon, resulting in a uniform coefficient of friction. Elevated p v levels led to the failure of less rigid polyurethane materials. The results allowed for a ranking and performance comparison of the PU materials. Materials with lower Young’s modulus exhibited accelerated delamination from the core layer due to shear forces induced by their flexible response and deformation. Furthermore, inherent air voids in the cured PU acted as sub-surface initiation points for damage, contributing to pitting and delamination. Ensuring adequate Young’s modulus and optimizing production technologies are critical for improving material performance. This study provides valuable insights into wear mechanisms, surface degradation, and lifetime behavior of candidate materials for WEC applications. By enhancing material performance and durability, the operational efficiency and service life of WEC systems can be extended, while environmental pollution caused by delaminated debris can be minimized. These findings support the development of more sustainable PU materials, aiding manufacturers and researchers in meeting stricter environmental regulations.